The Relationship between Intra-Industry Foreign Direct Investment and Intra-Industry Trade in China - Lyu, Licai; Blandford, David (Panoeconomicus, 2018)
This paper explores the relationship between intra-industry investment (III) and intra-industry trade (IIT) using cointegration and the Granger causality test. The empirical results indicate that there is a long-run equilibrium cointegration relationship between III and IIT in Chinese agriculture, manufacturing, the service sector and industry as a whole, and that this relationship is negative. Unidirectional Granger causality runs from III to IIT in manufacturing, the service sector and industry as a whole, but there is no strong evidence of causality running from IIT to III in any industry in China. Key words: Intra-industry foreign direct investment, Intra-industry trade, Cointegration, Granger causality. JEL: F14, F21, F23. Odnos između intra-industrijskih stranih direktnih investicija i intra-industrijske trgovine u Kini U radu se istražuje odnos između intra-industrijske investicije (III) i intra-industrijske trgovine (IIT) koristeći kointegraciju i Grangerov test uzročnosti. Empirijski rezultati pokazuju da postoji dugoročna kointegraciona ravnoteža između III i IIT u kineskoj poljoprivredi, proizvodnji, sektoru usluga i industriji u celini, i da je ovaj odnos negativan. Jednosmerna Grangerova uzročnost kreće se od III do IIT u proizvodnji, uslužnom sektoru i industriji kao celini, ali nema jakih dokaza o uzročnosti od IIT do III u bilo kojoj industriji u Kini. Ključne reči: Intra-industrijska direktna strana ulaganja, intra-industrijska trgovina, kointegracija, Grangerova uzročnost.